Long Term Storage of Isolates of Rhizoctonia Solani, a Mycelial Fungus - Jaap Keijer; Petra M. Houterman; Annette M. Dullemans; Marja G. Korsman (Fungal Genetics Reports, 1996)
Long term storage of R. solani was improved by using the freezing and thawing conditions that are generally used for animal/human cell lines. Key factors to success were the use of controlled freezing and the use of complete mycelial colonies.